Law Amending and supplementing a number of articles of the Law on complaints and denunciations - The National Assembly (2005)
This Law amends and supplements a number of articles of the December 2, 1998 Law on Complaints and Denunciations, which was amended and supplemented under the June 15, 2004 Law Amending and Supplementing a Number of Articles of the Law on Complaints and Denunciations